Crisis, (Non)Decision? From Carl Schmitt to Bartleby the Scrivener - Sferrazza Papa, Ernesto Calogero (Religija ir kultūra, 2013)
The article deals with the concept of “decision” related with the concept of “crisis” in Carl Schmitt’s thought. In the first part of the paper, I try to show why Carl Schmitt could be considered a “thinker of the crisis”, through the analysis of two of his major books: Die Diktatur (1921) and Politische Theologie (1922). In the second part, I show why “crisis” and “decision” are related in Schmitt’s doctrine. In the last part, I try to give a counter-reading of Schmitt’s decisionism through two literary characters: Bartleby the Scrivener and Mullah Nasrr Eddin. In this final part, the article discusses whether Giorgio Agamben’s theory of power can offer an adequate counterbalance for the dominant decisionist approach to the politics. My aim is to show how only an indecisionist approach could refuse the lexicon of the “crisis” in which our society lives.
Keywords: Carl Schmitt; crisis; decision; power; Giorgio Agamben